2021
DOI: 10.1101/2021.06.01.446621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biochemical insight into novel Rab-GEF activity of the mammalian TRAPPIII complex

Abstract: Transport Protein Particle complexes (TRAPP) are evolutionarily conserved regulators of membrane trafficking, with this mediated by their guanine nucleotide exchange factor (GEF) activity towards Rab GTPases. In metazoans evidence suggests that two different TRAPP complexes exist, TRAPPII and TRAPPIII. These two complexes share a common core of subunits, with complex specific subunits (TRAPPC9 and TRAPPC10 in TRAPPII and TRAPPC8, TRAPPC11, TRAPPC12, TRAPPC13 in TRAPPIII). TRAPPII and TRAPPIII have distinct spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The full-length Rab genes were used as previously described ( 36 , 37 ). The WDR44 gene was purchased from the DNASU plasmid repository (HsCD00296048).…”
Section: Methodsmentioning
confidence: 99%
“…The full-length Rab genes were used as previously described ( 36 , 37 ). The WDR44 gene was purchased from the DNASU plasmid repository (HsCD00296048).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that COPII as well as TRAPPIII complex proteins, which are both elevated in SCZ/BP synapses (Fig. 4G), can promote autophagy during nutrient stress (Tan et al, 2013; Jeong et al, 2018; Harris et al, 2021). These findings suggest that autophagy may be activated at SCZ and BP synapses.…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of speci c subunits of the TRAPP complexes contributed to the molecular processes between the ER-ERGIC-Golgi apparatus (21). Remarkably, two different complexes exist in metazoans and humans, TRAPP II and TRAPP III (9). One study about the cryo-EM structure of the metazoan TRAPP III demonstrated that two arms and one core of the complex exist.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main functions of these complexes is the tra cking interaction between the endoplasmic reticulum (ER), ER-Golgi intermediate compartment (ERGIC), and Golgi apparatus (3,4,7). Twenty years of subsequent research studies showed TRAPP complexes mediate the interaction between ER-exit-sites (COPI and COPII vesicles) through the Golgi apparatus (8) and show guanine nucleotide exchange factor (GEF) activity (9). This recent study showed that various conformational changes in the TRAPP complex have a vigorous GEF activity, including Rab1 and Rab11 interacting with TRAPP II, and particularly TRAPP III has a distinct speci city to Rab1 (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation